2006
DOI: 10.1016/j.jneuroim.2006.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Memory lineage relationships in HTLV-1-specific CD8+ cytotoxic T cells

Abstract: Cytotoxic memory T cells play a critical role in combating viral infections; however, in some diseases they may contribute to tissue damage. In HAM/TSP, HTLV-1 Tax 11-19+ cells proliferate spontaneously in vitro and can be tracked using the Tax 11-19 MHC Class I tetramer. Immediately ex vivo, these cells were a mix of CD45RA − /CCR7 − T EM and CD45RA + /CCR7 − T Diff memory CTL. The subsequent proliferating Tax 11-19 tetramer+ population expressed low levels of IL-7Rα, failed to respond to IL-7 and IL-15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
3
8
1
Order By: Relevance
“…3). This is contradictory to another study (58), which reported rapid ex vivo expansion of effector memory T cells in PBMCs of HAM/TSP patients in response to Tax. It is important to note that this study cultured the T cells for a longer duration compared to short 6 h stimulation in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…3). This is contradictory to another study (58), which reported rapid ex vivo expansion of effector memory T cells in PBMCs of HAM/TSP patients in response to Tax. It is important to note that this study cultured the T cells for a longer duration compared to short 6 h stimulation in our study.…”
Section: Discussioncontrasting
confidence: 97%
“…Indeed, we found a HTLV-2-specific CD8 ϩ T cell memory phenotype similar to that observed in HAM/TSP patients and in CMV infection, with high percentages of T EMRA cells (37,38). Whether this represents a particular differentiation phenotype associated with HTLV-2 infection or reflects a persistent activation and expansion of virus-specific CTLs remains to be determined.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we defined the memory phenotype of Tax-specific CD8 ϩ T cells from STLV-1-infected baboons based on the expression of CD45RA and the chemokine receptor CCR7 (50,51). To determine the memory phenotype of Tax-specific CD8 ϩ T cells, we stimulated PBMCs from 10 animals with their best-responding Tax peptide pool (usually pool 6 or 7) and assessed the expression of CD107a and cytokines.…”
Section: Cd8 ؉ T Cells From Several Stlv-1-infected Baboons Target Tamentioning
confidence: 99%